Metaverse-Based Celebration of the Chinese New Year 2024: A Mixed-Methods Survey Study - Xiaoling, Li; Wei, Chen (CV TOPAZART, 2024)
The Chinese New Year (CNY) is a globally recognized cultural festival celebrated by millions worldwide. In 2024, advancements in immersive technologies enabled celebrations to extend into the metaverse, offering a blend of traditional cultural practices with virtual and interactive experiences. This study examines user perceptions, engagement patterns, and cultural transmission in a metaverse-based CNY 2024 celebration. Using a mixed-methods approach, quantitative data were collected via structured surveys to assess participation metrics, while qualitative insights were obtained through in-depth interviews. Findings indicate that metaverse-based events can enhance cultural accessibility, foster global community interaction, and maintain cultural authenticity, while also facing challenges related to technological accessibility and digital literacy.